Does Quantitative Easing Affect People's Personal Financial Situation and Economic Inequality? The View of the German Population - Bernd Hayo (ZBW - Leibniz Information Centre for Economics, 2021)
Using representative survey data collected in 2018, I study how laypersons in Germany perceive the effects of quantitative easing (QE) on their personal financial situation and on national economic inequality. Almost 40% think that their economic situation is unaffected by QE, whereas 20% and 6% believe that QE has made them worse off or better off, respectively. Regarding economic inequality, about one-third of the population is of the opinion that QE contributes to inequality, only 10% think it does not, and 13% cannot perceive an impact. These groups with the different views are characterised using multivariate ordered logit models. First, respondents who feel that their personal economic situation has deteriorated as a result of QE tend to be savers, those with better objective knowledge about monetary policy affairs, and older people, whereas those who feel their situation has improved have more trust in the ECB and support conservative (CDU/CSU) parties. Second, the view that QE increases economic inequality in Germany is favoured by Left Party supporters, East Germans, and those with a relatively high level of monetary policy knowledge, whereas those who have more trust in the ECB have the opposite view. Third, persons with a high level of monetary policy knowledge, more formal education, and clear political preferences are more likely to answer the questions on the effects of QE.
Keywords: E58; E71; D31; Z1; 330; Economic inequality; income distribution; quantitative easing; QE; monetary policy; ECB; population survey; Germany